Primer of diagnostic imaging (Elsevier, 2011)
Primer of Diagnostic Imaging, "the purple book," gives you a comprehensive, up-to-date look at diagnostic imaging in an easy-to-read, bulleted format. Drs. Ralph Weissleder, Jack Wittenberg, Mukesh Harisinghani, and John W. Chen combine detailed illustrations and images with guidance on the latest applications of PET, CTA, and MRA into a portable resource for convenient reference wherever you go. Online access at www.expertconsult.com makes it even easier to tap into the guidance you need to survive your radiology residency.